2021
DOI: 10.1088/1674-1056/abe118
|View full text |Cite
|
Sign up to set email alerts
|

Low-threshold bistable reflection assisted by oscillating wave interaction with Kerr nonlinear medium*

Abstract: Owing to the enormously enhanced oscillating wave, a minute variation of the incident light intensity will give rise to a change in the dielectric constant of the Kerr nonlinear medium and lead to a bistable reflection with an ultra-low threshold intensity, which is closely related to the angle of incidence and the thickness of the Kerr nonlinear medium. The criterion for the existence of optical bistability is derived. Our bistability scheme is simple and not limited to the TM-polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It is demonstrated that the ultrahigh-order modes [15] excited in a symmetrical metal-cladding waveguide (SMCW) are highly sensitive to the variation of structural parameters [16] and the generated oscillating wave in the guiding layer can enhance the light-matter interaction, e.g., the Raman scattering [17] , the RGB lasing [18] , and the optical bistability [19] . By adding a thinner planar waveguide on the SMCW, the so-called double metal-dielectric-metal waveguides (DMDMW) structure is formed and the realized asymmetric Fano reflectivity curve is capable of getting giant GH shifts with a strong reflected beam intensity [20] .…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the ultrahigh-order modes [15] excited in a symmetrical metal-cladding waveguide (SMCW) are highly sensitive to the variation of structural parameters [16] and the generated oscillating wave in the guiding layer can enhance the light-matter interaction, e.g., the Raman scattering [17] , the RGB lasing [18] , and the optical bistability [19] . By adding a thinner planar waveguide on the SMCW, the so-called double metal-dielectric-metal waveguides (DMDMW) structure is formed and the realized asymmetric Fano reflectivity curve is capable of getting giant GH shifts with a strong reflected beam intensity [20] .…”
Section: Introductionmentioning
confidence: 99%